Subtotal colectomy for ulcerative colitis: lessons learned from a tertiary centre. (May 2017) - Buchs, N. C.; Bloemendaal, A. L. A.; Wood, C. P. J.; Travis, S.; Mortensen, N. J.; Guy, R. J.; George, B. D.
Abstract: Aim: Subtotal colectomy (STC) is a well‐established treatment for complicated and refractory ulcerative colitis (UC). A laparoscopic approach offers potentially improved outcomes. The aim of the study was to report our experience with STC for UC in a single large centre. Method: From January 2007 to May 2015, all consecutive patients undergoing STC for UC were retrospectively analysed from a prospectively managed database. Patients with known Crohn's disease or those undergoing one‐stage procedures were excluded. Demographics, perioperative outcomes and second‐stage procedures were analysed. Results: During the study period, 151 STCs were performed for UC [100 emergency (66%) and 51 elective (34%)]. Acute severe colitis refractory to therapy was the most common indication (62%). Overall, 117 laparoscopic (78%) and 34 open STCs were performed, with a conversion rate of 14.5%. Mortality and morbidity rates were 0.7% and 38%, respectively. Whilst operative time was shorter for open STC (by 75 min; P  =   0.001), there were fewer complications (32% vs 62%; P  =   0.002) and a shorter hospital stay (by 6.9 days; P  =   0.0002) following laparoscopic STC. Fewer complications and shorter hospital stay were also observed after elective STC. Patients undergoing laparoscopic STC were more likely to undergo a restorative second‐stage procedure than those having open STC (75% vs 50%; P  =   0.03). Conclusion: Laparoscopic STC for UC is feasible and safe, even in the emergency situation. A laparoscopic approach may offer advantages in terms of lower morbidity and reduced length of stay. Elective resection may offer similar advantages and is best performed whenever possible.